2009
DOI: 10.1590/s1413-24782009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Escolarização em assentamentos no estado de São Paulo: uma análise da Pesquisa Nacional de Educação na Reforma Agrária 2004

Abstract: O estudo sobre a escolarização nos assentamentos rurais do estado de São Paulo, com base nos dados da Pesquisa Nacional de Educação na Reforma Agrária 2004, constatou que o direito à educação só estava assegurado às crianças que frequentavam as séries iniciais do ensino fundamental; nos demais níveis e modalidades, inclusive a educação de jovens e adultos, a oferta escolar é insuficiente. O analfabetismo absoluto alcança 12% da população jovem e adulta e 40% dela têm, no máximo, quatro anos de estudos. Só há c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…In 2004, this trend was still confirmed, since the majority of the student population in the settlements attended schools in the urban area (DI PIERRO; ANDRADE, 2009). In São Paulo, for example, only 30% of the settlements were served by rural schools (DI PIERRO;ANDRADE, 2009).…”
Section: Education Conditions In Rural Settlements In Brazilmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2004, this trend was still confirmed, since the majority of the student population in the settlements attended schools in the urban area (DI PIERRO; ANDRADE, 2009). In São Paulo, for example, only 30% of the settlements were served by rural schools (DI PIERRO;ANDRADE, 2009).…”
Section: Education Conditions In Rural Settlements In Brazilmentioning
confidence: 99%
“…A study carried out in rural settlements in the state of São Paulo, based on the National Research on Education in Agrarian Reform (Pesquisa Nacional Sobre a Educação na Reforma Agrária [PNERA]), showed that there are difficulties in accessing early childhood education and that one quarter of young people between 15 and 19 years old were out of school (DI PIERRO; ANDRADE, 2009). A total of 75% of young people and adults attended federal or state agrotechnical schools.…”
Section: Education Conditions In Rural Settlements In Brazilmentioning
confidence: 99%
See 2 more Smart Citations
“…...] não só contraria a legislação e normas vigentes (que asseguram a crianças e adolescentes o estudo próximo à residência, em escolas com organização adequada, currículo relevante e práticas pedagógicas significativas), como entra em contradição com os projetos de formação humana das novas gerações e as aspirações de mudança nas relações político-econômicas, socioculturais e ambientais dos movimentos sociais do campo. Também inviabiliza a participação das famílias assentadas na gestão escolar, seja porque as escolas rurais têm pouca autonomia ou porque, em virtude da distância, as famílias não conseguem participar da gestão das escolas urbanas (DI PIERRO;. ANDRADE, 2009, p. 255).Ressaltamos ainda, a questão da permanência e dificuldades dos alunos na escola, acerca do acesso à escola, principalmente quando se trata do deslocamento escolar destes estudantes com necessidades especiais, pois sabemos muitas vezes chega a ser um problema, para os mesmos poderem se deslocar.…”
unclassified